Immobilization of Bacterial Cells on Natural Minerals for Self-Healing Cement-Based Materials - Sandalci, Ilgin; Tezer, Mustafa Mert; Basaran Bundur, Zeynep (Frontiers in Built Environment, 2021)
Environmental concerns related to concrete production is more pronounced with the recent Green Deal Policy and Paris Agreement. While concrete is intrinsically with low embodied energy materials, the large volume of cement production mean they account for approximately 8% of global emissions and significantly impact the global warming. In this perspective, utilization of biological resources can offer solution to the construction industry to mitigate the concerns related to climate change. Microbial induced calcium carbonate precipitation (MICP) is a promising technology to tackle the environmental burdens in the field. Recent research in the field of concrete materials suggested that it might be possible to develop a smart cement-based material that is capable of remediate cracks by MICP, enabling design of cement-based systems with prolongated service life without using hazardous chemical additives. However, the main challenge of the application is to extend the viability of the cells against restrictive environment of cement-paste. These cells have to tolerate highly alkaline conditions of cement paste, can survive the mixing process, and can remain viable with limited access to nutrients. This paper summarizes a study undertaken to investigate the self-healing efficiency of Sporosarcina pasteurii (S. pasteurii) cells immobilized on zeolite and sepiolite minerals. This study proposes a simple and economically feasible approach by immobilizing active vegetative cells on partially reactive minerals triggering faster crack remediation (less than 30 days). To obtain the bio-additive, the bacterial cells were immobilized on without nutrients and additional nutrients were only provided in curing stage after crack initiation. Screening of the healing process was done with ultrasonic pulse velocity (UPV) testing and stereomicroscopy. Further evaluation on performance was by evaluating the decrease in water absorption capacity. With this approach, the cracks on mortar surface were sealed and the water absorption capacity of the so-called self-healed mortar decreased compared to its counterpart cracked mortar samples.